Mesenchymal Stromal Cells Derived From Crohn's Patients Deploy Indoleamine 2,3-dioxygenase-mediated Immune Suppression, Independent of Autophagy - Chinnadurai, Raghavan; Copland, Ian B; Ng, Spencer; Garcia, Marco; Prasad, Mahadev; Arafat, Dalia; Gibson, Greg; Kugathasan, Subra; Galipeau, Jacques (Molecular therapy, 2015)
Autologous bone marrow-derived mesenchymal stromal cells (MSCs) for adoptive cell therapy of luminal Crohn's disease (CD) are being tested in clinical trials. However, CD is associated with dysregulation of autophagy and its effect on MSC's immunobiology is unknown. Here, we demonstrate no quantitative difference in phenotype, in vitro growth kinetics and molecular signatures to IFNγ between MSCs derived from CD and healthy individuals. CD MSCs were indistinguishable from those derived from healthy controls at inhibiting T-cell proliferation through an indoleamine 2,3-dioxygenase (IDO)-dependent mechanism. Upon IFNγ prelicensing, both MSC populations inhibit T-cell effector functions. Neither a single-nucleotide polymorphism (SNP) rs7820268 in the IDO gene, nor a widely reported CD predisposing SNP ATG16L1rs2241880 modulated the suppressive function of MSCs carrying these haplotypes. IFNγ stimulation or coculture with activated T cells upregulated the expression of autophagy genes and/or vacuoles on MSCs. Pharmacological blockade of autophagy pathway did not reverse the immunosuppressive properties and IFNγ responsiveness of MSCs confirming the absence of a functional link between these two cell biochemical properties. We conclude that autophagy, but not IDO and IFNγ responsiveness, is dispensable for MSC's immunosuppressive properties. MSCs from CD subjects are functionally analogous to those of healthy individuals.